2017
DOI: 10.1371/journal.pone.0180741
|View full text |Cite
|
Sign up to set email alerts
|

Genetic mapping of the LOBED LEAF 1 (ClLL1) gene to a 127.6-kb region in watermelon (Citrullus lanatus L.)

Abstract: The lobed leaf character is a unique morphologic trait in crops, featuring many potential advantages for agricultural productivity. Although the majority of watermelon varieties feature lobed leaves, the genetic factors responsible for lobed leaf formation remain elusive. The F2:3 leaf shape segregating population offers the opportunity to study the underlying mechanism of lobed leaf formation in watermelon. Genetic analysis revealed that a single dominant allele (designated ClLL1) controlled the lobed leaf tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 41 publications
1
22
0
Order By: Relevance
“…In recent years, the combination of a bulked segregant analysis (BSA) and next-generation sequencing technology (BSA-Seq) has been widely applied to identify candidate genes controlling important agronomic traits in watermelon, such as dwarf phenotype 37 40 , lobed leaves 41 , yellow skin 42 , fruit shape 43 , fruit pigment accumulation 44 and anthracnose resistance 45 . In this study, we investigated the inheritance of watermelon dwarf genes in the F 2 population of ‘w106’ (dwarf) × ‘Charleston Gray’ (CG; vine), which indicated that the dwarf phenotype was controlled by a single recessive gene.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the combination of a bulked segregant analysis (BSA) and next-generation sequencing technology (BSA-Seq) has been widely applied to identify candidate genes controlling important agronomic traits in watermelon, such as dwarf phenotype 37 40 , lobed leaves 41 , yellow skin 42 , fruit shape 43 , fruit pigment accumulation 44 and anthracnose resistance 45 . In this study, we investigated the inheritance of watermelon dwarf genes in the F 2 population of ‘w106’ (dwarf) × ‘Charleston Gray’ (CG; vine), which indicated that the dwarf phenotype was controlled by a single recessive gene.…”
Section: Introductionmentioning
confidence: 99%
“…With the advancement of next‐generation sequencing (NGS) technology, sequencing‐based gene mining strategies, such as bulk segregant analysis (BSA), genetic mapping and genome‐wide association study (GWAS), have been widely used as affordable, efficient and routine approaches to dissect crop traits in rice (Wang et al , ) tomato (Chapman et al , ; Soyk et al , ), cucumber(Li et al , ; Xu et al , ), peanut(Luo et al , ), chickpea(Deokar et al , ),spinach(She et al , ), apple(Jia et al , ) and melon (Hu et al , ). Recently, genes or QTLs related to sugar transporter (Ren et al , ), dwarfism (Dong et al , ) and lobed leaves (Wei et al , ) have been reported in watermelon. However, the genetic dissection of rind hardness has not been reported and remains a knowledge gap in fresh fruits such as watermelon.…”
Section: Introductionmentioning
confidence: 99%
“…The non-lobed leaf trait can be used as a morphological marker for maintenance of parental lines of hybrids as the character is recessive to normal lobed leaf. This is governed by a single dominant gene ( ClLL1 ) situated on chromosome 4 (Wei et al ., 2017). Though sweetness and flesh colour are the two most important traits that strongly influence consumer preference (Kyriacou et al ., 2017); fruit shape, stripe pattern and as well as seed colour also stands as one of the key acceptance determining traits.…”
Section: Discussionmentioning
confidence: 99%